Marianne A. Ferber, Julie A. Nelson (eds.). Más allá del hombre económico. Madrid: Cátedra, 2004. - Ojeda Monroy, Pioquinto Ricardo (Cuestiones de Género: de la igualdad y la diferencia, 2006)
Más allá del hombre económico. Marianne A. Ferber, Julie A. Nelson (eds.). Madrid: Cátedra, 2004.